Faktor-Faktor yang Berhubungan dengan Pemberian Imunisasi Hepatitis B 0-7 Hari - Laila Kusumawati, Nenny Sri Mulyani, Dibyo Pramono (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: According to WHO, Indonesia is a middle and high hepatitis B endemic country with children as its most common carriers. The risk of developing chronic hepatitis is higher (90%) if children are infected in their early age. Early hepatitis B immunization program by providing first dose within 7 days after birth was implemented in Bantul District, but the coverage was still lower (68,17%) than expected.Objective: To identify factors associated with providing hepatitis B immunization first dose 0-7 days after birth.Methods: This cross sectional study was conducted in Bantul District. Interview was conducted among 213 mothers who have babies of 8 days to 23 months old. Subjects were recruited using with stratified random sampling method at 3 subdistricts with different immunization coverage. Chi square and logistic regressions were used for data analysis.Results: The univariate analysis showed factors that have significant relationship: birth attendants (OR:4,01, 95% CI:1,49-10,85), birth place (OR:2,25, 95% CI:1,00-5,02), perceived severity of disease (OR:2,27, 95%CI:1,06-4,95) and health worker services (OR:2,34, 95% CI:1,20-4,57). Multivariate analysis with logistic regression model showed that only birth attendant, health worker services and perceived severity of disease have significant relationship with providing hepatitis B immunization on 0-7 days.Conclusions: Birth attendants, health worker services and perceived severity of disease are associated with providing hepatitis B immunization first dose within seven days after birth.Keywords: immunization, hepatitis B, first dose within 7 days